Kritik Terhadap Penyelesaian Tindak Pidana Pembunuhan Dengan Mekanisme Restorative Justice - Natalia, Christina Lintang; Ardian, Riswanda (Universitas Medan Area, 2024)
The research aims to show that murder cases should not be resolved by deviating from Criminal Procedure Law or using non-formal legal mechanisms. The focus of this issue is on KOMNAS HAM Number: 22/HM.00/IV/2023, where a murder case was settled through a non-formal legal mechanism. Ideally, this murder case should have been resolved through the Criminal Procedure process and other applicable internal regulations of law enforcement agencies. This article uses normative research methods that examine document studies using secondary data such as laws and regulations. Specifically, this research will address the contradiction between what should be and what is (das sollen and das sein). Das sollen refers to the general legal provisions or normative realities. Murder is a criminal offense that results in the loss of a person's life. As a regular crime (delik biasa), the legal process against the suspect must continue. This creates a conflict in a case that occurred in Wamena, Papua, on February 23, 2023, where a murder committed by law enforcement officers was resolved through a non-formal legal mechanism, which also involved human rights violations.